Dynamic coupling between the central and autonomic cardiac nervous systems in patients with refractory epilepsy: A pilot study - Melo, Eline; Fiel, José; Milhomens, Rodrigo; Ribeiro, Thaynara; Navegantes, Raphael; Gomes, Francinaldo; Duarte Gomes, Bruno; Pereira, Antonio (Frontiers in Neurology, 2022)
The heart and brain are reciprocally interconnected and engage in two-way communication for homeostatic regulation. Epilepsy is considered a network disease that also affects the autonomic nervous system (ANS). Fluctuations in the brain arousal system reflect the activity of the ANS. The neurovisceral integration model (NVM) proposes that cardiac vagal tone, indexed by heart rate variability (HRV), can indicate the functional integrity of cognitive neural networks. ANS activity and the pattern of oscillatory EEG activity covary during the transition of arousal states and associations between cortical and autonomic activity are reflected by HRV. Cognitive dysfunction is one of the common comorbidities that occur in epilepsy, including memory, attention, and processing difficulties. Recent studies have shown evidence for the active involvement of alpha activity in cognitive processes through its active role in the control of neural excitability in the cortex through top‐down modulation of cortical networks. In the present pilot study, we evaluated the association between resting EEG oscillatory behavior and ANS function in patients with refractory epilepsy. Our results show: 1) in patients with refractory epilepsy, there is a strong positive correlation between HRV and the power of cortical oscillatory cortical activity in all studied bands (delta, theta, alpha, and beta) in several regions of interest in both hemispheres, the opposite pattern found in controls which had no or negative correlation between the variables; 3) higher heartbeat evoked potential amplitudes in patients with refractory epilepsy than in controls. Taken together, these results point to a significant alteration in heart-brain interaction in patients with refractory epilepsy.